Spiritual Experience, Religious Orientation, and Self-Reported Behavior - Reinert, Duane F. (The international journal for the psychology of religion, 2000)
This study found evidence to support the validity of the revised Spiritual Experience Index (Genia, 1997) as an instrument to gauge spiritual experience within a developmental framework. The Spiritual Experience Index's Spiritual Support subscale is related to engaging in formal religious practices, having God consciousness, and having an intrinsic orientation to religion. The Spiritual Openness subscale is related to, but also distinct from, quest orientation. Spiritual openness tended to be inversely related to involvement in formal religious practices among conservative Christians. There was evidence to support Genia's (1997) developmental spiritual typology of growth-oriented, transitional, dogmatic, and underdeveloped.